Umweltschutz in lernenden Organisationen: Theoretische und methodische Grundlagen akteurs- und umsetzungsorientierter Forschungskonzepte. Am Beispiel des Kooperations-Projektes Lokal handeln - systemweit denken. Beschäftigungs-, Qualifizierungs- und Beteiligungspotentiale von Umweltmanagement-systemen in kleinen und mittleren Unternehmen. Zukunftsfähige Unternehmen (6) - Helmut Brentel (Wuppertal Institut für Klima, Umwelt, Energie, 2000)
– This Wuppertal Paper Environmental Protection in Learning Organizationshighlights the crucial methodological and theoretical assumptions which influencedand formed the design of the ADAPT-project about SMEs - Sustainability and theneeds of employees. Potentials for employment, qualification and participation of environmental management systems in small and medium-sized companies. ADAPT is a Community Initiative financed by funds of the European Social Fund (ESF) and by the Land North Rhine-Westphalia (NRW). ADAPT helps companiesand employees of the European Union to adapt structural changes in the industrial environment. The project is an European transfer project which analyses andcompares business experience in implementing environmental protection measureswith the premises of EMAS/ISO 14000. The primary aim of the project is toimprove participation and qualification in environmental management.The paper discusses the state of research and the future development necessities fora social science based design of environmental management systems and the improvement of sociological consulting practices. The project aims especially on the development and testing of new tools for environmental management systems whichenable corporate actors and practitioners much better to understand and to usetechniques of self-evaluation and continuous self-improvement implemented by theintervening researchers.After some initial thesis about future capabilities of enterprises, about challenges ofsocial science based environmental research and the relation of researchers andpractitioners in chapter 1, chapter 2 gives a brief overall view of the projects phasesand the methodology used. Chapter 3 focusses more detailed on the methodologicalbackground of the projekt design, particularly on action research and qualitativesocial science research and chapter 4 focusses on the theoretical assumptions, especially on the importance of micropolitic approaches and the analysis ofcollective action in the works of Michel Crozier and Erhard Friedberg and the organizational learning approach in the works of Chris Argyris and Donald A.Schön. The final chapter 5 draws - in relation to contemporary approaches andresearch on corporate environmental protection, micropolitics and organizationallearning - some first conclusions from the experiences made during the projectsproceedings.
urn:nbn:de:bsz:wup4-opus-11055
Keywords: 330; Betriebsökologie; Instrumente sozial-ökologischer Folgenabschätzung; lernendes Unternehmen; Mikropolitik; Organisationsforschung; Selbstevaluation; sozialwissenschaftliche Beratung; Umweltmanagementsysteme; actionable knowledge; collective action; corporate environmentalism; design for environment; EMAS; environmental management systems; learning organizations; micropolitics; organizational learning; sustainable development; Umweltmanagement; Lernende Organisation; Umweltforschung; Theorie